Detection and quantification of pathogens in saliva of adolescents with cerebral palsy: a cross-sectional study - Yoshida, Rosemeire Arai; Lobato, Tiago Bertola; Gorjão, Renata; França, Lucas Santiago; Alves, Lívia Araujo; Santos, Maria Teresa Botti Rodrigues (Frontiers in Dental Medicine, 2023)
Background Elevated levels of inflammatory mediators in saliva have been described in individuals with cerebral palsy (CP). Objective The aim of this study was to detect and quantify the pathogens Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum and Prevotella intermedia in the saliva of adolescents with CP. Methods This is a cross-sectional study with adolescents with CP to detect periodontopathogens from saliva samples. Initially, saliva was collected from the CP (n = 34) and control groups (n = 31), followed by the gingival index (GI) for distribution of the groups of individuals with CP and control with gingivitis (bleeding on probing ≥ 10%) and without gingivitis. Bacterial DNA was extracted from saliva samples for detection of periodontopathogens by quantitative PCR (q-PCR). Data were analyzed by Mann–Whitney and Kruskal–Wallis tests, analysis of variance t-test (ANOVA) with Tukey–Kramer post-hoc tests (p < 0.05). Results The quantification of DNA of periodontopathogens in saliva samples showed that adolescents with CP present a variability (22.93–39.56) in the detection of P. gingivalis and that some subjects with CP and gingivitis (n = 4) present high quantification of P. gingivalis (ranging 39.56–37.65), although no significant difference was found between the groups (p > 0.05). A significant contrast was observed for the pathogen P. intermedia when comparing the difference in the control group (p = 0.0396). No major differences were detected in the quantification of periodontopathogens evaluated between the control group and CP. Conclusion Adolescents with CP showed variability in the detection of DNA of periodontopathogens, especially a great variation in the detection of P gingivalis in saliva of CP with gingivitis.